IMPLEMENTASI SISTEM PLTS HYBRID PLN SEBAGAI SUMBER ENERGI PADA PENGERING BIJI KOPI SOLAR DRYER DOME - Rozak, Ojak ABdul; Astuti, Rini; Muallim, Edwar; Rhomadon, Ahmad Arif Falah (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Implementation of the design of a hybrid solar power plant (PLTS) system as the main energy source in drying coffee beans (solar dryer dome). Efficient and sustainable drying of coffee beans is a challenge for many coffee farmers, especially in remote areas with limited access to conventional energy sources. With a hybrid solar power system, it is hoped that environmentally friendly and cost-effective solutions can be created with electrical energy. This hybrid solar power plant combines solar technology with PLN energy sources or batteries as a storage medium for electrical energy. The solar dryer dome is a special greenhouse for the coffee bean drying process, allowing optimal microclimate control, so that the coffee bean drying process can run faster and more evenly without depending on weather conditions. The planning, design, assembly, commissioning, implementation, testing, and analysis process has been well done from start to finish. The Hybrid Solar Power System can supply batteries for charging for 4 hours with a sunlight intensity of 415 lux and a maximum temperature of 50.5°C. The battery can be used discharging for 1.5 hours with a load of 0.5 amperes with a voltage drop of 0.01 volts. With this Hybrid Solar Power Plant, the solar dryer dome system can be supplied with energy continuously according to its operational needs.